Workers' Birth Control Group (1927)
1927 1927 1920s 4 pages At the National Conference of Labour Women held in May, the following Resolution was carried almost unanimously, in an audience of over 1,000 women delegates. “That this Conference, while in no criticising the view of those, who, for scientific or moral reasons, are opposed to the practice of Birth Control, expresses its opinion that the Ministry of Health should permit Health Authorities to provide for those who desire it, information on the subject of Birth Control, and that in cases where Local Health Authorities desire to give such information, the Ministry of Health should not, on that account, withhold the usual grants.” All workers’ organisations are urged to send a similar resolution to the Minister of Health and their local M.P., and to approach their local health authorities and maternity committees with deputations and resolutions. MEMBERSHIP FORM. WORKERS’ BIRTH CONTROL GROUP. I herewith enclose application for Membership, and ........ being my Subscription for the year 1927, and Donation of.......... Name.............................................. Address............................................ Organisation ................ Date................ NOTE. — In view of the smallness of the Subscription (intentionally small to allow ALL to join) we earnestly hope Donations, will, wherever possible, be included to help to cover our necessary expenses. 292/840/1/11